Association Between the Managerial Ability and Long-Term Performance in Mergers and Acquisitions - Adinda Ayu Jelita Putri; Diah Hari Suryaningrum (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Mergers and acquisitions are still a hot topic to be discussed and are often seen as a high priority issue worldwide as a controversial decision because it has a very complex impact. This study aims to test and analyze whether managerial ability has an effect on long-term performance and 1, 2, and 3 years after mergers and acquisitions. In addition, this study also aims to examine whether managerial ability in horizontal acquisitions has an effect on long-term operating performance rather than diversified acquisitions. This research uses quantitative research. The sample of this research is 14 public acquisition companies with a research period of 10, 9, and 8 years after mergers and acquisitions are listed on the Indonesia Stock Exchange and KPPU in 2010-2012. The results showed that managerial ability had an effect on operating performance 1 year after mergers and acquisitions. Other research results indicate that managerial ability has no effect on operating performance 2 and 3 years after mergers and acquisitions and long-term performance. In addition, managerial ability in horizontal acquisitions has no effect on long-term performance and 1, 2, and 3 years after mergers and acquisitions than diversified acquisitions..